Acquiring Expertise in Radiology: Studies on Development & Assessment of Image Interpretation Skills - van der Gijp, A. (Utrecht University, 2017)
Radiological image interpretation is a complex skill and requires years of training to master. To improve education and performance in radiological image interpretation, it is key to understand visual diagnostic reasoning. The role of medical images in clinical decision-making is increasingly important and medical imaging techniques are developing very quickly. One of the most crucial developments in radiology has been the introduction of digital volumetric imaging, allowing radiologists to navigate through thin cross sections on a computer monitor instead of viewing two-dimensional hard-copy images on a light box. This development has changed the nature of the visual diagnostic task. How this development affects the visual diagnostic reasoning process and how we should align our training and assessment methods is largely unknown and is the subject of this thesis. We investigated which knowledge and skills are important for the development of expertise in radiological 2D and volumetric image interpretation and contributed to the development and evaluation of training and assessment methods to stimulate expertise development in radiological 2D and volumetric image interpretation. We identified knowledge and skills that are required for 2D and volumetric image interpretation. The main components of image interpretation were: perception, analysis, and synthesis. The knowledge and skills required for 2D image interpretation differed from those required for volumetric image interpretation: perception was dominant in volumetric image interpretation, while synthesis was dominant in 2D image interpretation. Visual search patterns differ across various levels of expertise and we found that search strategy training can improve volumetric image interpretation performance of trainees. The results contribute to the development of radiology training and assessment methods by providing several tools. We developed a framework of knowledge and skills that can be used as a guideline for developing radiology education, for example as a template for learning objectives or test blueprints. For teaching and assessing volumetric image interpretation skills, it is important to realize that the construct differs from 2D image interpretation. Two assessment methods were developed: a method that can be used to gain insight into error types and performance of learners and a method that can increase the authenticity of image interpretation assessment. These methods can be used in radiology education to stimulate the development of image interpretation expertise.
Keywords: Medical Education; Radiology; Image Perception; Radiology Education; Visual Problem Solving